RELATIONSHIP OF SMOKING BEHAVIOR WITH HYPERTENSION EVENTS IN NEGLASARI HEALTH CENTER BANDUNG CITY - Agung Sutriyawan (Universitas Wiralodra, 2019)
Hypertension is a degenerative disease that usually occurs and has a fairly high mortality rate and affects the quality of life and productivity of a person. The nicotine contained in cigarettes caused feelings of dependence or called nicotine dependence. Besides, nicotine also causes myocardial irritability. Hormones in the blood serum cause vasoconstriction blood vessels, it makes the blood pressure to rise. The purpose of this study was to relationship of smoking behavior with hypertension events in Neglasari Health Center Bandung City. The research method used is quantitative analytic type, with cross sectional research design. Total population of this study was 8072 people aged > 18 years and living in the Neglasari village. The sample of 74 respondents using purposive sampling technique. Analysis technique used is chi square test. The results of this study indicate that half of Neglasari residents have hypertension (54,3%). The analysis showed that there was a relationship between smoking behavior and the incidence of hypertension (p value = 0.008). It is recommended that Puskesmas conduct Posbindu PTM activities and conduct counseling on the dangers of smoking in order to increase health efforts in the Neglasari puskesmas work area.